2014
DOI: 10.1080/1070289x.2014.950970
|View full text |Cite
|
Sign up to set email alerts
|

Can stigma become a resource? The mobilisation of aesthetic–corporal capital by female immigrant entrepreneurs from Brazil

Abstract: The proportion and visibility of Brazilian women and particularly the specific images of Brazil and Brazilians in the Portuguese imaginary have contributed to the construction of new versions of stigma and stereotypes surrounding them. Mainstream images of Brazilian women have incorporated prejudices about the sensuality of Creole women who are reminiscent of the Portuguese colonial imaginary. Starting from this stigmatised image, we show how Brazilian women entrepreneurs in the 'beauty' business filière reint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Other authors have already reported that there is an attribution of hypersexuality to Brazilian women by European society. As already mentioned in different studies (PADILLA, 2014;BADET, 2016), many Brazilians are victims of problems directly related to the themes of gender and sexuality in the countries where they decided to immigrate. In Spain, where there is a significant presence of Brazilian immigrants, the different research works point to the construction of a stereotyped image of Brazil.…”
Section: Discussionmentioning
confidence: 91%
“…Other authors have already reported that there is an attribution of hypersexuality to Brazilian women by European society. As already mentioned in different studies (PADILLA, 2014;BADET, 2016), many Brazilians are victims of problems directly related to the themes of gender and sexuality in the countries where they decided to immigrate. In Spain, where there is a significant presence of Brazilian immigrants, the different research works point to the construction of a stereotyped image of Brazil.…”
Section: Discussionmentioning
confidence: 91%
“…Em termos de violência de gênero, as mulheres imigrantes relatam sobre baixos salários, machismo cotidiano, assédio moral e sexual e corpo visto como objeto. As violências parecem ser agravadas pela nacionalidade, em razão do estereótipo de sensualidade ligado à imagem da brasileira ;França, 2012;França & Oliveira, 2021;Malheiros & Padilla, 2015). Uma dificuldade comum, especialmente para as mais jovens, é conseguir alugar um quarto.…”
Section: Segunda Categoria: Classeunclassified
“…However, she could not work as a teacher because her Brazilian qualifications were not recognised and because of racism: "the Spanish discriminate a lot against immigrants, and especially, if you don't speak their language, it's as if you did not even exist". She also reported a specific aspect of feminised precarity experienced by Brazilian women who were often perceived as hyper-sexualized linked with colonial racialized and gendered exoticization of identities among the Spanish who "have this paradigm, Brazilian women, they see us as, well always as sexual objects … you have to be careful not to dress sensually" (Malheiros and Padilla 2015). Sexualised racism was also identified among other Latin Americans.…”
Section: Economic Precarity Among Latin Americans Was Widespread On Arrival In Southernmentioning
confidence: 99%